Applications of Fuzzy Logic in Plasma Physics: Uncertainty Management in Fusion Research: Advancements in Uncertainty Management in Fusion Research using Fuzzy Logic (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research paper explores the application of fuzzy logic in uncertainty management withinthe context of plasma physics and fusion research. Plasma confinement, stability, and precise diagnosticmeasurements are paramount in achieving controlled nuclear fusion. However, the dynamic and uncertainnature of plasma conditions presents challenges. This study presents findings that highlight theeffectiveness of fuzzy logic-based control systems in addressing these challenges. By dynamicallyadapting to changing plasma conditions, fuzzy logic enhances plasma stability, improves diagnosticaccuracy, and provides valuable insights into fusion experiment optimization. The practical implicationsinclude improved fusion reactor design, enhanced plasma confinement strategies, and increasedefficiency in fusion experiments. This research signifies a significant step toward the realization ofpractical fusion energy production.